Normativni vidik slovenščine v 3. tisočletju - knjižna slovenščina med realnostjo in idealnostjo - Tivadar, Hotimir (Slavistična revija, 2010)
The Slovene (standard) language is often considered by both the expert community and lay public to be a difficult code to acquire, presenting considerable difficulties for speakers of various dialects, which is also stated in Toporišič's Slovene grammar. On the other hand, it is also belived -probaly due to its presumed inconsistency and difficulty - to be losing its prestige. The analysis of its vowels, which is presented in the article, demonstrates just the opposite, i.e., the uniform standard language fulfills its function in the ideal form in practice witout regard ti the dialectal diversity of its speakers.
Keywords: 21.st.; fonetika; govorjeni jezik; jezikovna norma; knjižni jezik; medijski jezik; phonetics; samoglasniki; Slovene; slovenščina; standard language